Pemanfaatan Ekstrak Daun Mangrove (Rhizophora mucronata sp.) dengan Variasi Pelarut Sebagai Bahan Aktif Sediaan Farmasi Terapi Anti Kanker - Anita Ratna Faoziyah; Wahyu Kurniawan (LPPM STIKES Guna Bangsa, 2017)
This research was done to study mangrove leaves (Rhizophora mucronata sp.) utilization in the Cilacap regency brackish waters. The research goal is to make nano emulsion from mangrove plants as an alternative to increase the economic value of mangrove. This research method has 2 phases. In the first phase, mangrove leaves was extracted using various solvent. In the second phase mangrove leaves extract was formulated as nano emulsion as anti-cancer treatment along as an alternative to increase mangrove leaves economic value. Extraction results of mangrove leaves using various solvent such as hexane, ethyl acetate and ethanol show that using ethanol p.a solvent with the young leaves of mangrove giving the highest amount extract as much as 18.24%. Mangrove leaves extract nano emulsion can be prepared using Self-Nano Emulsifying Drug Delivery System (SNEDDS) technique. The SNEDDS technique nano emulsion formulation started with 14 formulas. The best formula from this study was using Tween 80 : PEG 400 : Fish Oil as much as 6 ml: 1 ml: 1 ml dosage ratio. Using the best formula, it was added with 5 mg of mangrove leaves extract. The result test of Drug Loading, calculation of Emulsification Time and Dissolution test show that mangrove leaves extract has the potential to be used as an active substance anti-cancer on nano emulsion manufacturing.